Pengaruh Karakteristik Perusahaan terhadap Book Tax Differences - Mardohar Tua Tampubolon; Ely Kartikaningdyah (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2016)
This study aims to analyze the effect association between firm level characteristics (i.e size, profitability, earnings quality, liquidity, leverage) and Book Tax Difference (BTD). We predict that larger, higher profitability, lower earnings quality, higher leverage and lower liquidity firms will have larger BTD. The sample used were non-financial companies listed on Indonesia stock exchange in 2010 to 2013. The data collection method using purposive sampling method and data used are panel data. Regression used is ordinary least squares regression (OLS) with fix effect model. The result showed that largerand higher profitability firms will have a larger BTD. This finding is consistent with political power of large corporations. Moreover, we find that firms with low earnings quality will have a large BTD. Moreover, that firms with low earnings quality will have a large BTD, However, we find no association between leverage and liquidity irrespective of variability of BTD.